La Défaillance De La Clientèle Du Micro Crédit Au Maroc : Méthodes Des Scores - Abdillah, Kadouri; Lotfi, Benazzou; Bennis, Laila (European Scientific Journal, ESJ, 2016)
The development of microfinance in Morocco dates from the 1990s and is particularly dynamic in the years 2000. Currently, and like other sectors of finance, the microfinance knows the same difficulties concerning the rate of covering. Indeed, credit risk or non-recovery of debts is likely to hinder the development of micro-finance institutions. Thus, an important place should be reserved for the business management of credit risks of borrowers notably through the anticipation of their failure. This anticipation is achievable through the use of a technical score that can affect an individual in a group, namely the right customers and failing. Drawing on the lessons of the discrimination function provided by (Saporta, 1975), judgment can be made by socio-economic and demographic characteristics of each customer and given the form taken by different variables. Calculating scores allowed us to develop a discriminating filter to note clients, identify risk classes and identify those likely to fall.